Skin organ culture: a review - Kataranovski, M... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1999)
Short-term organ culture of skin explants is a useful model for research into various aspects of skin biology. The use of skin organ culture systems in defining factors which affect homeostasis in elucidating modulatory effects ofbiologic response modifiers, drugs and physical agents on the skin and in studying complex aspects of cutaneous biology in normal and diseased skin is reviewed. Our own data regarding organ culture of rat full-thickness skin explants have been presented in this review.
Keywords: Dinitrochlorobenzene; Drug effects; Growth and development; Inflammation; Inflammation mediators; Keratinocytes; Pathology; Psoriasis; Retinoids; Skin; Tissue culture; Tumor necrosis factor